Advances in reforming and partial oxidation of hydrocarbons for hydrogen production and fuel cell applications. (February 2018) - Sengodan, Sivaprakash; Lan, Rong; Humphreys, John; Du, Dongwei; Xu, Wei; Wang, Huanting; Tao, Shanwen
Abstract: One of the most attractive routes for the production of hydrogen or syngas for use in fuel cell applications is the reforming and partial oxidation of hydrocarbons. The use of hydrocarbons in high temperature fuel cells is achieved through either external or internal reforming. Reforming and partial oxidation catalysis to convert hydrocarbons to hydrogen rich syngas plays an important role in fuel processing technology. The current research in the area of reforming and partial oxidation of methane, methanol and ethanol includes catalysts for reforming and oxidation, methods of catalyst synthesis, and the effective utilization of fuel for both external and internal reforming processes. In this paper the recent progress in these areas of research is reviewed along with the reforming of liquid hydrocarbons, from this an overview of the current best performing catalysts for the reforming and partial oxidizing of hydrocarbons for hydrogen production is summarized.